OC-078 Evaluating innovative surgery: a nested ideal phase 2 study within an external randomised pilot (the romio trial). (22nd June 2015) - Barham, P; Berrisford, R; Titcomb, D; Hollowood, A; Sanders, G; Streets, C; Wheatley, T; Avery, K; Hanna, G; Metcalfe, C; Blazeby, JM
Abstract : Introduction: There is a need for well designed and conducted pragmatic randomised controlled trials (RCTs) of open and minimally invasive approaches for oesophageal cancer, but totally minimally invasive techniques are still evolving. The NIHR ROMIO pilot RCT was designed to inform a definitive trial. This paper describes how the ROMIO Study informed the main trial design and incorporated a nested IDEAL (Idea, Development, Evaluation, Assessment and Long-term evaluation of innovative surgery) Phase 2a evaluation of totally minimally invasive oesophagectomy (TMIO). Method: The pilot ROMIO trial was conducted in two centres. In one centre (with a team of 3 surgeons) patients were randomised to open gastric mobilisation and right thoracotomy (open surgery) or laparoscopic gastric mobilisation and right thoractomy (hybrid surgery) and in the other centre (team of 6 surgeons) patients were randomised into three groups, also including totally TMIO. The surgical protocol for open and hybrid surgery was agreed and monitored during the trial, where as the protocol for TMIO was deliberately flexible to monitor development of the technique and to document changes in the procedure and collect prospective data. Results: During 20 months of recruitment, 256 patients were assessed for eligibility, 132 (52%) were found to be eligible and 101 (76.5%) agreed to participate. A high proportion of patients received their randomised allocation (87%). Dressing patients with large bandages, covering all possible incisions, was successful in keeping patients blind whilst pain was assessed during the first week post-surgery (patients were unable to guess the type of surgery they had received). In the TMIO group three-phase surgery was undertaken by three of the six surgeons in one centre. This evolved to two-phase TMIO surgery with continuing modifications to the anastomotic technique. During the study period the national audit data showed that only 14% of oesophagectomies are TMIO. Conclusion: Rapid recruitment to the pilot ROMIO trial and the successful refinement of methodology indicated that a definitive two group trial comparing open and hybrid surgery is feasible. Techniques for TMIO are however still evolving and the procedure is not widely undertaken. The main ROMIO trial, therefore, is designed within a continuing IDEAL Phase 2b study to monitor when this complex technique has stabilised and ready for full evaluation within a pragmatic trial design. Disclosure of interest: None Declared.